Prediction Of Disease Burden And Healthcare Resource Utilization Through Simple Predictive Analytics Using Mathematical Approaches, An Experience From University Of Malaya Medical Centre - Amirah Azzeri; Nur Farhan Abdul Hakim; Mohd Hafiz Jaafar; Maznah Dahlui; Sajaratulnisah Othman; Tunku Kamarul Zaman Tunku Zainol Abidin (Faculty of Medicine, Universiti Malaya, 2024)
Indexed by MyCite